Current consult : (Lange Medical Books/McGraw-Hill, 2006)
This latest addition to the Lange Current Series features alphabetically-organized, easy-to-read, two-page bulleted spreads covering everything from syndromes and symptoms to diagnosis and treatment for all areas of cardiology. This information-packed quick reference is perfect for busy clinicians who don't have the time to consult with large references or online databases that are too comprehensive for their immediate treatment needs.